Notch signaling regulates gastric antral LGR5 stem cell function. (12th August 2015) - Demitrack, Elise S; Gifford, Gail B; Keeley, Theresa M; Carulli, Alexis J; VanDussen, Kelli L; Thomas, Dafydd; Giordano, Thomas J; Liu, Zhenyi; Kopan, Raphael; Samuelson, Linda C
Abstract The major signaling pathways regulating gastric stem cells are unknown. Here we report that Notch signaling is essential for homeostasis of LGR5+ antral stem cells. Pathway inhibition reduced proliferation of gastric stem and progenitor cells, while activation increased proliferation. Notch dysregulation also altered differentiation, with inhibition inducing mucous and endocrine cell differentiation while activation reduced differentiation. Analysis of gastric organoids demonstrated that Notch signaling was intrinsic to the epithelium and regulated growth. Furthermore, in vivo Notch manipulation affected the efficiency of organoid initiation from glands and single Lgr5‐GFP stem cells, suggesting regulation of stem cell function. Strikingly, constitutive Notch activation in LGR5+ stem cells induced tissue expansion via antral gland fission. Lineage tracing using a multi‐colored reporter demonstrated that Notch‐activated stem cells rapidly generate monoclonal glands, suggesting a competitive advantage over unmanipulated stem cells. Notch activation was associated with increased mTOR signaling, and mTORC1 inhibition normalized NICD‐induced increases in proliferation and gland fission. Chronic Notch activation induced undifferentiated, hyper‐proliferative polyps, suggesting that aberrant activation of Notch in gastric stem cells may contribute to gastric tumorigenesis.